Mastering research methods - Chua, Yan Piaw (McGraw-Hill Education, 2012)
Mastering Research Methods is a practical guide that covers all aspects of research methodology. It is a useful teaching and learning tool for courses related to research at both undergraduate and postgraduate levels. This book can also be used as a reference by researchers when they are conducting and reporting their research. Concepts are explained in detail with examples to enable readers to carry out confidently each stage of the research process. Exercises are provided at the end of each chapter to help readers reinforce their understanding of the topics covered in the chapter.